2021
DOI: 10.5498/wjp.v11.i12.1301
|View full text |Cite
|
Sign up to set email alerts
|

BDNF methylation and mRNA expression in brain and blood of completed suicides in Slovenia

Abstract: BACKGROUND Suicide is a major public health problem. Worldwide, around 800000 people die by suicide every year. Suicide is a multifactorial disorder, with numerous environmental and genetic risk factors involved. Among the candidate genes, changes in the BDNF locus at the gene, epigenetic, mRNA, and protein expression levels have been implicated in psychiatric disorders, including suicidal behavior and completed suicides. AIM To investigate ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, hypomethylation of the BDNF region upstream of exon I has been found in blood samples of suicide victims. In contrast, no differences in DNA methylation were observed in the hippocampus or the DLPFCx [190].…”
Section: Dna Methylation Alterations In Peripheral Blood Tissuesmentioning
confidence: 65%
“…However, hypomethylation of the BDNF region upstream of exon I has been found in blood samples of suicide victims. In contrast, no differences in DNA methylation were observed in the hippocampus or the DLPFCx [190].…”
Section: Dna Methylation Alterations In Peripheral Blood Tissuesmentioning
confidence: 65%
“…The most commonly studied gene system was BDNF ( N = 10, including two studies investigating the TrkB.T1 gene; Kang et al, 2018; Ropret, Kouter, Zupanc, & Videtic Paska, 2021; Roy, Shelton, & Dwivedi, 2017; Kim et al, 2015; Kim et al, 2014; Maussion et al, 2014; Kang et al, 2013; Keller et al, 2011; Keller et al, 2010; Ernst et al, 2009). Of the eight studies examining methylation specifically in the BDNF gene, six found BDNF hypermethylation to be implicated across a range of SITB outcomes, while one study of SI found no group differences (Roy, Wang, Palkovits, Faludi, & Dwivedi, 2017), and an SD study found hypomethylation (Ropret et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, regarding the average methylation level across the Kang et al, 2013;Keller et al, 2011;Keller et al, 2010;. Of the eight studies examining methylation specifically in the BDNF gene, six found BDNF hypermethylation to be implicated across a range of SITB outcomes, while one study of SI found no group differences (Roy, Wang, Palkovits, Faludi, & Dwivedi, 2017), and an SD study found hypomethylation (Ropret et al, 2021).…”
Section: Epigenome-wide Association Studiesmentioning
confidence: 99%
“…[31][32][33] Reduced BDNF expression can affect the recovery of neurological function in PSD patients, while increased BDNF expression can reduce the accumulation of free radicals, alleviate attacks on neurons, improve the pathological state of neurons, and restore neurological function. [34,35] Extensive evidence suggested that the excessive secretion of glucocorticoids and the decrease of central 5-HT levels are risk factors for depression. The pathogenesis of PSD is related to the dysfunction of the dopaminergic nerve, significantly decreasing 5-HT and norepinephrine levels, which may be an essential cause leading to PSD.…”
Section: Discussionmentioning
confidence: 99%